2021
DOI: 10.1002/adma.202104891
|View full text |Cite
|
Sign up to set email alerts
|

Molecule Confined Isolated Metal Sites Enable the Electrocatalytic Synthesis of Hydrogen Peroxide

Abstract: levels of waste chemicals. [3] Thus, developing green and cost-effective techniques for the direct synthesis of H 2 O 2 is an ongoing challenge.Being green and sustainable, electrochemical synthesis powered by renewable electricity is an attractive route for direct on-site production of H 2 O 2 . In this process, oxygen is catalytically reduced to H 2 O 2 through the two-electron (2e -) oxygen reduction reaction (ORR). [4] For efficient H 2 O 2 production, electrocatalysts with high activity and selectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 56 publications
0
50
0
Order By: Relevance
“…In conclusion, by combining the aforementioned XRD, STEM, XPS and XAS analysis, it is confirmed that the isolated W atoms with unique coordination structure of W 1 N 1 O 2 exist in W 1 /NO-C, rather than W nanoparticles/nanoclusters. It should be mentioned that, compared with traditional Fe, Co, Ni-based SACs with N coordination reported so far, [36,46,47,48] the as-obtained W 1 /NO-C features single-atom W metal center and unsaturated terdentate N 1 O 2 coordination environment. Such distinctive structures of W 1 / NO-C presumably contribute to distinct reaction selectivity and high-efficiency H 2 O 2 production, as will be discussed below.…”
Section: Resultsmentioning
confidence: 87%
“…In conclusion, by combining the aforementioned XRD, STEM, XPS and XAS analysis, it is confirmed that the isolated W atoms with unique coordination structure of W 1 N 1 O 2 exist in W 1 /NO-C, rather than W nanoparticles/nanoclusters. It should be mentioned that, compared with traditional Fe, Co, Ni-based SACs with N coordination reported so far, [36,46,47,48] the as-obtained W 1 /NO-C features single-atom W metal center and unsaturated terdentate N 1 O 2 coordination environment. Such distinctive structures of W 1 / NO-C presumably contribute to distinct reaction selectivity and high-efficiency H 2 O 2 production, as will be discussed below.…”
Section: Resultsmentioning
confidence: 87%
“…Nowadays, some of the state-of-the-art catalysts for the electrocatalytic production of H 2 O 2 are precious-metal-based and alloy materials ( e.g. , Pd-based, 10–12 Pt-based, 13 and Pd–Au 14,15 ), single-atom catalysts, 16–18 and carbon-based materials. 19,20 These catalysts exhibit high activity and selectivity in a wide voltage range.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, both reaction products are extremely useful, especially when they can occur exclusively. Because the ORR occurs on the surface of used catalyst, the selectivity of the reaction is closely related to the type and surface properties of the catalyst. The selectivity toward H 2 O 2 can be enhanced via careful catalyst design and fabrication. So it is a significant challenge and demand to develop electrocatalysts with high activity and selectivity in the selective formation of H 2 O 2 on account of the sluggish kinetics of ORR and the existence of competing 4e –1 ORR.…”
Section: Introductionmentioning
confidence: 99%